In Fitting Memory The Art and Politics of Holocaust Memorials - Milton, Sybil (Wayne State University Press, 2018)
In Fitting Memory, a critical survey of Holocaust memorials and monuments in Europe, Israel, and the United States, focuses on the archeological remains at the original sites of Nazi terror that constituted the first postwar memorials. The Holocaust is defined here as the collective designation for the Nazi mass murder of Jews, Gypsies, and the handicapped, and for the related persecution of Soviet prisoners of war and other ideological opponents. Featuring text and photographs, the book shows how, since 1945, memorials and monuments have served not only as secular shrines but also as temporal institutions reflecting changing public constituencies and distinctive political, social, and cultural contexts. Sybil Milton poses two vital and provocative questions about the memorials built since the end of World War II: to whose memory were they built and how fitting are they? The Holocaust is a sensitive subject whose representation demands accuracy and tact. This volume, the first study of the institutionalization of public memory, demonstrates how various nations, politicians, and designers have attempted to do justice to this subject in public art and sculpture, and shows how national origin, ethnic allegiance, political ideology, and prevailing artistic style determined how memorials were commissioned and installed. His book also provides an analysis of the complex interrelationship between authentic historic sites, disparate and ephemeral representations of history, and the changing political and aesthetic balance between commemoration and escapism. In Fitting Memory includes 127 specially commissioned photographs by Ira Nowinski from seven European countries, the United States, and Israel. Nine additional photographs are by photographers from Italy, the Netherlands, and the United States. The riveting images provide the reader with a visual tour of these memorials. Along with an annotated bibliography, the volume also contains a comprehensive list of memorials in Europe, the United States, and Israel. An essential tool for those interested in visiting the memorial sites, the book also provides a critical analysis for serious researchers.The Holocaust is a sensitive subject whose representation demands accuracy and tact. This volume, the first study of the institutionalization of public memory, demonstrates how various nations, politicians, and designers have attempted to do justice to this subject in public art and sculpture, and shows how national origin, ethnic allegiance, political ideology, and prevailing artistic style determined how memorials were commissioned and installed. This book also provides an analysis of the complex interrelationship between authentic historic sites, disparate and ephemeral representations of history, and the changing political and aesthetic balance between commemoration and escapism. In Fitting Memory includes 127 specially commissioned photographs by Ira Nowinski from seven European countries, the United States, and Israel. Nine additional photographs are by photographers from Italy, the Netherlands, and the United States. The riveting images provide the reader with a visual tour of these memorials. Along with an annotated bibliography, the volume also contains a comprehensive list of memorials in Europe, the United States, and Israel. An essential tool for those interested in visiting the memorial sites, the book also provides a critical analysis for serious researchers.